Pedestrian and Evacuation Dynamics 2008 - Klingsch, Wolfram W. F.; Rogsch, Christian; Schadschneider, Andreas; Schreckenberg, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The international conference on "Pedestrian and Evacuation Dynamics", held on February 27-29, 2008 at Wuppertal University in Germany, was the fourth in this series after successful meetings in Duisburg (2001), Greenwich (2003) and Vienna (2005). The conference was aimed at improving the scientific exchange between scientists, experts and practitioners of various fields of pedestrian and evacuation dynamics and featured: the analysis of evacuation processes and pedestrian motion, modeling of pedestrian dynamics in various situations, experiments on pedestrian dynamics, human behavior research, regulatory action. All these topics are included in this book to give a broad and state-of-the-art overview of pedestrian and evacuation dynamics.
Experiment and Evacuation -- Simulation and Modelling -- Psychology -- Miscellaneous.
Keywords: Mathematics; Animal behavior; Engineering; Civil engineering; Mathematics; Applications of Mathematics; Behavioural Sciences; Civil Engineering; Automotive Engineering